2017
DOI: 10.7764/rcia.v44i2.1691
|View full text |Cite
|
Sign up to set email alerts
|

Efecto combinado de la aplicación de riego y compost sobre la composición de la baya Montepulciano en un entorno volcánico de la región de Lacio (Italia central)

Abstract: Montepulciano red grape is cultivated in the northern part of the Latium region, primarily for the production of DOC "Colli Etruschi Viterbesi" structured wines for aging. In Mediterranean areas, viticulture is closely influenced by vine water status. In this context, the practice of irrigation may alleviate water-stress-related reductions in plant development to guarantee grape quality, especially in semi-arid areas. The application of on-farm compost in a vineyard may affect grape quality without negative ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…With respect to juice chemistry, Morlat (2008) report that total anthocyanins and TSS were decreased, while pH and K + were increased in berries following addition of high rates of composted manures. In contrast, in a 3-year investigation of irrigation strategies with and without compost addition, (Cirigliano et al, 2017) found improved anthocyanin and other polyphenol contents in berries following compost addition compared to treatments without compost. Their data suggest that in drip irrigated Mediterranean-type climates, compost application can improve grape quality over irrigation alone, perhaps due to better infiltration and water holding capacity in compost treated vines.…”
Section: Compost Use and Management For Improved Vineyard Soil Healthmentioning
confidence: 81%
“…With respect to juice chemistry, Morlat (2008) report that total anthocyanins and TSS were decreased, while pH and K + were increased in berries following addition of high rates of composted manures. In contrast, in a 3-year investigation of irrigation strategies with and without compost addition, (Cirigliano et al, 2017) found improved anthocyanin and other polyphenol contents in berries following compost addition compared to treatments without compost. Their data suggest that in drip irrigated Mediterranean-type climates, compost application can improve grape quality over irrigation alone, perhaps due to better infiltration and water holding capacity in compost treated vines.…”
Section: Compost Use and Management For Improved Vineyard Soil Healthmentioning
confidence: 81%
“…Most potential adaptations to water scarcity under future climate change have been evaluated individually. Our review suggests that the few existing studies dealing with combinations of adaptations help in identifying several compromises between these adaptations: the reduction of irrigation requirement through water-saving practices (Cirigliano et al, 2017 ; Chrysargyris et al, 2018 ; Gil et al, 2018 ; Romero et al, 2018 ; Torres et al, 2018 ); the benefits of cover crops despite water competition (Tomaz et al, 2017 ); the conservation of vineyard areas thanks to cultivar changes and new governance modalities (Galbreath, 2014 ; Delay et al, 2015 ; Zhu et al, 2016 ; Morales-Castilla et al, 2020 ); and the role of socio-economic conditions in promoting or regulating adaptations (Olen et al, 2016 ; Georgopoulou et al, 2017 ). It is noteworthy that since the systematic review ended, new developments have been published: Buesa et al ( 2020 ) confirm the positive effects of east-west row orientation on yields; Morales-Castilla et al ( 2020 ) quantified the reduction of suitable area lost thanks to late-ripening cultivar (from 56 to 24%); Phogat et al ( 2020 ) went further in the estimation of future irrigation water requirement and demonstrate the importance of reducing evaporation loss; while López-Urrea et al ( 2020 ) quantified the effect of organic and plastic mulch on evaporation.…”
Section: Discussionmentioning
confidence: 99%
“…Transparent plastic covering (TPC) has been reported to increase water use efficiency in vineyards in Brazil, by creating higher humidity and lowering evapotranspiration as compared to open field conditions (da Silva et al, 2018 ). The use of organic matter as compost increases the soil water storage capacity and reduces irrigation needs (Cirigliano et al, 2017 ). Tomaz et al ( 2017 ) showed that the presence of a cover crop under irrigated conditions forces the vine root system, mainly its thinner roots, to seek water in increasingly deeper soil.…”
Section: Adapting Viticulture To Future Water Scarcitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that the application of organic fertilizers, such as compost and manure, increases organic matter in the soil, representing a source of nutrients for agricultural production [9][10][11][12][13], and improves the agronomic characteristics of the soil. The application of compost to the soil increases its total cation exchange capacity as well as levels of potassium (K), calcium (Ca), and magnesium (Mg), among other nutrients [14].…”
Section: Introductionmentioning
confidence: 99%